Disimilaritas Ilmu Nahwu Mazhab Basrah dan Kufah serta Implikasinya terhadap Penerjemahan Al-Qur’an / The Dissimilarities Between The Nahwu Science of The Basrah and Kufah Sects Along with Their Implications for Translating Al-Qur'an - Fahmi Yahya Abdil Haq; Maman Abdurrahman; Asep Sopian (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2021)
يهدف هذا البحث إلى وصف بعض الاختلافات في النحو بين مدرستي البصرة والكوفة والتعرف على آثارها تجاه ترجمة القرآن. إن فهم الاختلاف في الرأي المرتبط بعلم النحو جزء لا يتجزأ من علم النحو نفسه. إن عدم فهم علم النحو يؤثر على فهم اللغة العربية. فهذه الحالة لا تتعلق فقط بالخطأ في إيصال الرسالة باللغة العربية كلغة اتصالية، ولكنها أيضًا تتعلق بالخطأ في قراءة آيات القرآن. وتشير نتائج هذا البحث إلى وجود اختلافات عديدة في قراءة آيات القرآن الكريم بين مدرستي البصرة والكوفة بناءً على قواعد النحو الخاصة بكل منهما. فتؤدي بعض الاختلافات في الرأي بين المدرستين إلى ظهور مفاهيم مختلفة بشأن الآيات القرآنية. وفي سياق ترجمة القرآن إلى اللغة الإندونيسية، فيبدو أن هناك العديد من الترجمات التي تتماشى مع مدرسة البصرة والأخرى تتعارض معها والعكس كذلك. فيأمل الباحثون أن يتمكن هذا البحث من جعل ترجمة القرآن إلى اللغة الإندونيسية أفضل وأكثر كمالًا استنادًا إلى مصادر موثوقة. الكلمات المفتاحية : البصرة؛ الاختلاف؛ الكوفة؛ ترجمة القرآن الكريم.Abstract:This research aims to identify some dissimilarities in the Nahwu sciences of the sects of Basrah and Kufah and their implications for the translation of the Qur'an. The understanding related to the dissimilarity of opinion in the science of Nahwu is an inseparable part of the science of Nahwu itself. The misunderstanding of Nahwu science has implications for the misinterpretation of Arabic. It does not only have an impact on misrepresenting the messages in Arabic as a tool of communication, but it also has an impact on misreading the Qur'an verses. The researcher researched library research to discuss the main problems and sub-problems that have been formulated. The results of this study indicated that there are several dissimilarities in reading the verses of the Qur'an between the Basrah and Kufah sects, which are in line with the dissimilarity of the Nahwu science on each of them. Some dissimilarities between the two schools of thought arise from the different understandings of the Qur'an verses. In the translation context of the Qur'an into Bahasa, it showed that several translations are in line with the Basrah school of thought, and several translations are in line with the Kufah sects. The researcher hopes that this article can translate the Qur'an into Indonesian better and more perfectly, based on reliable sources.